Percutaneous Spinal Needle–Assisted Suture Passing in Medial Meniscal Posterior Root Tear Repair - Ahmet Emin Okutan, Ph.D.; Serkan Surucu, Ph.D.; Kerim Öner, Ph.D.; Lokman Kehribar, Ph.D. (Arthroscopy Techniques, 2025)
The medial meniscal posterior root (MMPR) is essential for absorbing hoop stress and preventing meniscal extrusion. MMPR tears lead to significant alterations in knee joint kinematics, increasing tibiofemoral contact pressure and accelerating knee osteoarthritis. Given the poor prognosis of untreated meniscal root tears, there has been growing interest in surgical repair techniques. The percutaneous spinal needle–assisted suture-passing technique offers a cost-effective, minimally invasive alternative that reduces iatrogenic damage to articular cartilage and eliminates the need for medial collateral ligament release compared with currently widely used suture passers. This technique allows for precise suture placement and minimizes meniscal injury during suture passing, providing a promising option for repair of the MMPR tear.